Elevated Wall Shear Stress in Aortic Type B Dissection May Relate to Retrograde Aortic Type A Dissection: A Computational Fluid Dynamics Pilot Study. (September 2017) - Osswald, A.; Karmonik, C.; Anderson, J.R.; Rengier, F.; Karck, M.; Engelke, J.; Kallenbach, K.; Kotelis, D.; Partovi, S.; Böckler, D.; Ruhparwar, A.
Abstract : Objective: Retrograde aortic type A dissection (RTAD) is a known complication in patients with aortic type B dissection. The purpose of this computational fluid dynamics (CFD) study was to identify haemodynamic risk factors for the occurrence of RTAD. Methods: Computed tomographic angiography (CTA) images of 10 patients with type B dissections, who subsequently developed a RTAD, were retrospectively analysed together with patients constituting a control group ( n  = 10) where no further vascular events after the initial type B dissection occurred. CFD simulations were conducted based on 3D surface models of the aortic lumen derived from CTA datasets. For both groups, pressures, velocity magnitudes and wall shear stress (WSS) were compared at the site of the future RTAD entry tear and the surrounding aortic wall. Results: WSS at the site of the future entry tear was significantly elevated compared with the surrounding wall (15.10 Pa vs. 5.15 Pa, p  < .001) and was significantly higher in the RTAD group than in the control group (6.05 Pa, p  < .002). Pressures and velocity magnitudes were not significantly elevated at the entry tear (3825.8 Pa, 0.63 m/s) compared with the aortic arch (3549.8 Pa, 0.50 m/s) or control group (3501.7 Pa, 0.62 m/s). Conclusions: Increased WSS accompanies the occurrence of RTAD. The results merit the design for a prospective study to confirm whether WSS is a risk factor for the occurrence of RTAD.